Treaty-making from an indigenous perspective : a ned’u’ten-canadian treaty model - McCue, Lorna June (Allard Research Commons, 2009)
This thesis argues that the Ned'u'ten, an indigenous people, have the right to decolonize and self-determine their political and legal status at the international level. The Ned'u'ten are currently negotiating a new relationship with Canada and are considering various treaty models to achieve this goal. This thesis advocates principles for a peace treaty model that accomplishes both Ned'u'ten decolonization and self-determination. The first chapter of this thesis demonstrates that indigenous perspectives in legal culture are diverse and not homogeneous. My Ned'u'ten perspective on treaty-making contributes to these perspectives. The second chapter challenges the legitimacy of the Canadian state, over Ned'u'ten subjects and territories. This is accomplished through the rejection of dispossession doctrines that Canada has used to justify colonial and oppressive practices against the Ned'u'ten. Decolonization principles are prescribed in this chapter. The third chapter takes a historical view of the right to self-determination and shows how state practice, indigenous peoples' participation, and international scholars have attempted to articulate the scope and content of this right in the contemporary context of indigenous self-determination. A Ned'u'ten self-determination framework is proposed based on indigenous formulations of the right to self-determination. Self-determination principles are also prescribed in this chapter. The final chapter compares two cases where indigenous peoples in Canada are attempting to create a new relationship with the state: the James Bay Cree and "First Nations" in the British Columbia Treaty Commission Process. This comparison will show that the degree of participation that indigenous peoples have in implementing their rights to self-determination, will determine the parameters of any new relationship that indigenous peoples create with the state. Negotiating principles are prescribed for a Ned'u'ten-Canada relationship as well as a peace treaty process to accomplish this goal. It is my thesis that the Ned'u'ten and Canada can achieve a peaceful and balanced relationship through the peace treaty model I propose.